1
$\begingroup$

As seen in Section 4 of Chapter 5 of Costello, K. "Renormalization and Effective Field Theory", or in section 5.2 $L_\infty$-Algebras of Classical Field Theories and the Batalin-Vilkovisky Formalism, the BV form of the Chern-Simons action is $$S=\frac{1}{2}\langle A,dA\rangle+\frac{1}{6}\langle A,[A\wedge A]\rangle+\langle A^*,D_Ac\rangle+\frac{1}{2}\langle c^*,[c,c]\rangle,\tag{1}$$ with $c\in\Omega^0(M)\otimes\mathfrak{g}[1]$, $A\in\Omega^1(M)\otimes\mathfrak{g}$, $A^*\in\Omega^2(M)\otimes\mathfrak{g}[-1]$, and $c^*\in\Omega^3(M)\otimes\mathfrak{g}[-2]$. In here $\mathfrak{g}$ is a Lie algebra equipped with an invariant non-degenerate pairing $\langle\cdot,\cdot\rangle$. However, in the first reference it is also claimed that this action can be put into the form $$S=\frac{1}{2}\langle e,de\rangle+\frac{1}{6}\langle e,[e\wedge e]\rangle\tag{2}$$ for some field $e$. I don't see how this is possible.

Let me explain my reasoning. Let us first assume $e=c+A+A^*+c^*$. Note that $\langle\alpha,\beta\rangle=0$ if $\alpha\in\Omega^p(M)\otimes\mathfrak g$ and $\beta\in\Omega^q(M)\otimes\mathfrak g$ with $p+q\neq 3$. We can use this to expand $\langle e,d{e}\rangle$. For example, the only term that can be coupled with the $A$ coming from the left $e$ is the $d{A}$ coming from $d{e}$. We conclude that \begin{equation} \frac{1}{2}\langle e,d{e}\rangle=\frac{1}{2}\langle c,d{A^*}\rangle+\frac{1}{2}\langle A,d{A}\rangle+\frac{1}{2}\langle A^*,d{c}\rangle.\tag{3} \end{equation} Now, remembering that $A^*$ and $c$ are fermionic, we have \begin{equation} \begin{aligned} \langle c,d{A^*}\rangle&=\int c^ad{A^{*b}}\langle T_a,T_b\rangle_{\mathfrak g}=-\int d{A^{*b}}c^a\langle T_a,T_b\rangle_{\mathfrak g}\\ &=-\int d{(A^{*b}c^a)}\langle T_a,T_b\rangle_{\mathfrak g}+\int A^{*b}d{c^a}\langle T_a,T_b\rangle_{\mathfrak g}. \end{aligned}\tag{4} \end{equation} Thus, up to total derivatives we have \begin{equation} \frac{1}{2}\langle e,d{e}\rangle=\frac{1}{2}\langle A,d{A}\rangle+\langle A^*,d{c}\rangle.\tag{5} \end{equation}

To expand the term $\langle e,[e\wedge e]\rangle$, note that $[e\wedge e]$ can only have even forms. Indeed, an odd form in the expansion of $[e\wedge e]$ must come from the coupling $[\alpha\wedge\beta]$ of an odd form $\alpha$ and an even form $\beta$ in $e$. Since they are different, the term $[\beta\wedge\alpha]$ also appears in the expansion of $e$. Now, all even forms in $e$ are fermionic while all odd forms in $e$ are bosonic. We conclude that $\alpha$ is bosonic while $\beta$ is fermionic. Therefore \begin{equation} [\alpha\wedge\beta]=\alpha^a\wedge\beta^b[T_a,T_b]=\beta^b\wedge\alpha^a[T_a,T_b]=-\beta^b\wedge\alpha^a[T_b,T_a]=-[\beta\wedge\alpha].\tag{6} \end{equation} Therefore the terms $[\alpha\wedge\beta]$ and $[\beta\wedge\alpha]$ cancel. By the same token, the rest of the surviving terms in the expansion of $[e\wedge e]$ are symmetric $[\alpha\wedge\beta]=[\beta\wedge\alpha]$. Given that we are in three dimensions, they have to either be 0-forms or 2-forms. We conclude that \begin{equation} [e\wedge e]=[c\wedge c]+2[c\wedge A^*]+[A\wedge A].\tag{7} \end{equation} Of course, for $0$-forms we have $[c\wedge c]=[c,c]$. The second term is then
\begin{equation} \frac{1}{6}\langle e,[e\wedge e]\rangle=\frac{1}{6}\langle A,[A\wedge A]\rangle+\frac{1}{3}\langle A,[c\wedge A^*]\rangle+\frac{1}{6}\langle c^*,[c\wedge c]\rangle.\tag{8} \end{equation}

We see that we have failed to recover our original action because of some factors. One could try to resolve this by combining the fields in $e$ with different numerical factors. However, since the action of $A$ already has the correct factors, we cannot rescale $A$. Indeed, any rescaling of $A$ would produce a mismatch in the scales of the quadratic and cubic terms in $A$. On the other hand, the term $\langle A^*,dc\rangle$ has also the correct factor, so that we must scale $c$ and $A^*$ inversely. This means that we will never get the correct factor for the cubic term in $c$, $A$, and $A^*$.

$\endgroup$
  • $\begingroup$ Which page in the first reference for claim? Which eqs? $\endgroup$ – Qmechanic Jul 22 at 20:53
  • $\begingroup$ I realized that it is not only Section 4.1 but section 4. All that I am saying is in page 161 of bookstore.ams.org/surv-170. $\endgroup$ – Iván Mauricio Burbano Jul 22 at 21:12
  • $\begingroup$ As another problem that I just realized, the term $\langle A,[c\wedge A^*]\rangle$ differs from the correct $\langle A^*,[A,c]\rangle$ by a sign. If one looks at the second reference, they do take that sign into account. But then the sign of their $\langle A^*,dc\rangle$ term is wrong. $\endgroup$ – Iván Mauricio Burbano Jul 22 at 21:17
  • $\begingroup$ For starters, which coefficients are off by more than a sign? $\endgroup$ – Qmechanic Jul 22 at 21:33
  • $\begingroup$ The coefficient $\langle A,[c\wedge A^*]\rangle$ appears with a $1/3$ instead of a $1$ in the action of the field $e$. Similarly, the coefficient of $\langle c^*,[c\wedge c]\rangle$ appears with a $1/6$ instead of a $1/2$. $\endgroup$ – Iván Mauricio Burbano Jul 22 at 21:35
0
$\begingroup$

In this answer we will focus on the cubic term, which seems to be OP's main question.

  1. The trilinear form $$t\equiv\langle\cdot,[\cdot,\cdot]\rangle: \mathfrak{g}\times \mathfrak{g}\times\mathfrak{g}\to \mathbb{C}\tag{A}$$ is totally antisymmetric, because the bilinear form $\langle\cdot,\cdot\rangle$ is invariant/associative.

  2. Consider fields ${\bf e}$ that are both Lie-algebra-valued, form-valued & supernumber-valued. Note that in OP's references the $n$-forms are (implicitly) interpreted as carrying Grassmann-degree $n$ (modulo 2). The total Grassmann-parity of the fields ${\bf e}$ is assumed to be odd, so that such fields anti-commute (in the appropriate graded symmetric tensor algebra). The trilinear form $t$ therefore becomes totally symmetric wrt. such fields.

  3. In BV-CS theory (before gauge-fixing), we consider a minimal field $$ {\bf e} ~=~ c ~+~\underbrace{A_{\mu}\mathrm{d}x^{\mu}}_{=~{\bf A}}~+~\underbrace{A^{\ast\mu}(\star \mathrm{d}x)_{\mu}}_{=~{\bf A}^{\ast}} ~+~\underbrace{c^{\ast}\Omega}_{=~{\bf c}^{\ast}} \tag{B}$$ of above type, where $$(\star \mathrm{d}x)_{\mu}~:=~\frac{1}{2}\epsilon_{\mu\nu\lambda}\mathrm{d}x^{\nu}\wedge \mathrm{d}x^{\lambda}\tag{C}$$ and where $$\Omega~:=~\frac{1}{6}\epsilon_{\mu\nu\lambda}\mathrm{d}x^{\mu}\wedge\mathrm{d}x^{\nu}\wedge \mathrm{d}x^{\lambda} ~=~\frac{1}{3}\mathrm{d}x^{\mu}\wedge(\star \mathrm{d}x)_{\mu}.\tag{D}$$ (The wedges will be not be written explicitly from now on.)

  4. The cubic action term is a multinomial expression $$\begin{align} \left. \frac{1}{6} t({\bf e},{\bf e},{\bf e})\right|_{\text{top-form}}~=~& \frac{1}{6}t({\bf A},{\bf A},{\bf A})+ t({\bf A}^{\ast},{\bf A},c) +\frac{1}{2}t({\bf c}^{\ast},c,c)\cr ~=~&\left( t(A_1,A_2,A_3)+ t(A^{\ast\mu},A_{\mu},c) +\frac{1}{2}t(c^{\ast},c,c)\right) \Omega.\end{align}\tag{E}$$ Note that the (reciprocal) coefficient of each term of eq. (E) is precisely its symmetry factor. Eq. (E) agrees with OP's eq. (1).

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ The problem with that hint is that some of these terms cancel. For example, in the expansion of $\langle e,[e\wedge e]\rangle$ we get both the term $\langle A^*, [A\wedge c]\rangle$ and the term $\langle A^*,[c\wedge A]\rangle$. However these two terms cancel. Indeed, in a basis of $\mathfrak{g}$ we have $A^ac^b[T_a,T_b]=c^bA^a[T_a,T_b]=-c^bA^a[T_b,T_a]$, so that $[A\wedge c]=-[c\wedge A]$. $\endgroup$ – Iván Mauricio Burbano Jul 22 at 23:03
  • $\begingroup$ Terms add up rather than cancel. I updated the answer. $\endgroup$ – Qmechanic Jul 23 at 6:57
  • $\begingroup$ I still don't understand the answer. Let us focus on the cubic $A^*,A,c$ terms. We have $t(e,e,e)=\cdots t(A^*,A,c)+t(A^*,c,A)+t(c,A^*,A)+t(c,A,A^*)+t(A,c,A^*)+t(A,A^*,c)\cdots$. It seems to me that you are claiming that these 6 terms give the same result. This is not the case. The first two terms cancel because of my first comment. The second two terms cancel because of a similar reason. Finally, the last two terms are equal (the antisymmetry of $t$ on the Lie algebra does not remain intact at the level of the forms since we have the super graduation and the form graduation). $\endgroup$ – Iván Mauricio Burbano Jul 23 at 13:19
  • $\begingroup$ Just to exaplain myself better, the last two terms survive because, while the Lie algebra part gives a minus sign, the fact that $A^*$ and $c$ are fermions also gives a minus sign. The overall sign is then positive when exchanging these two terms. $\endgroup$ – Iván Mauricio Burbano Jul 23 at 13:25
  • $\begingroup$ I just studied your answer better and I found the root of the problem in your answer. Let me denote by $\deg$ the homological degree of the field mod 2, so that $\deg A=\deg c^*=0$ and $\deg c=\deg A^*=1$. On the other hand, let me denote by $|\cdot|$ the form degree of the field mod 2, so that $|A|=|c^*|=1$ and $|c|=|A^*|=0$. Your argument seems to use something like $FG=(-1)^{(|F|+\deg F)(|G|+\deg G)}GF$. That is, a field $F$ is bosonic or fermionic according to its total degree. That is not the case here however. Instead $FG=(-1)^{|F||G|+\deg F\deg G}GF$ is the correct formula. $\endgroup$ – Iván Mauricio Burbano Jul 23 at 14:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.